Differential effects of angiotensin II receptor blocker and losartan/hydrochlorothiazide combination on central blood pressure and augmentation index. (July 2015) - Metoki, Hirohito; Obara, Taku; Asayama, Kei; Satoh, Michihiro; Hosaka, Miki; Elnagar, Noha; Miyawaki, Yoshinori; Kojima, Iwao; Ohkubo, Takayoshi; Imai, Yutaka; for the Japan-Home versus Office Blood Pressure Measurement Evaluation – Augmentation Index Study Investigators
Abstract Central systolic blood pressure (CSBP) may be a better predictor of cardiovascular risk than clinic brachial (B)SBP. The effects of dose increment from medium dose of angiotensin II receptor blockers (ARBs) to the maximum dose of ARBs (maximum) and changing from medium dose of ARBs to losartan 50 mg/hydrochlorothiazide 12.5 mg combination (combination) were compared in hypertensive patients in whom monotherapy with a medium ARB dose did not achieve goal home SBP (135 mmHg). Four weeks after treatment with a medium ARB dose monotherapy, those whose home SBP level was above 135 mmHg were randomized to receive the maximum ARB dose (n = 101) or the combination (n = 99) once daily for 8 weeks. Both regimens significantly decreased BSBP and CSBP, while a decrease in BSBP and CSBP was greater with combination. The maximum significantly decreased augmentation index (AIx), while the combination did not. The rate of a decrease in reflection to decrease in CSBP was greater in the maximum than in the combination. In the elderly subgroup, the combination more effectively lowered BSBP than the maximum, and only the combination decreased CSBP. However, in the young subgroup, the maximum decreased AIx more than combination, while both regimens lowered CSBP and BSBP to a similar extent. It is explained in part that the maximum may affect pulse wave reflection more predominantly than the combination, especially in young subjects. A weak effect on pulse wave reflection and, thus, on CSBP, of the combination may be overcome by the potent antihypertensive effect of this regimen.